Preinvasive nonhost resistance of Arabidopsis against melanized appressorium-mediated entry of multiple nonadapted Colletotrichum fungi - Hiroki Irieda (Plant Signaling & Behavior, 2022)
Nonhost plants effectively block a vast number of nonadapted fungal pathogens at the preinvasive stage. On the host plants, adapted fungal pathogens such as Colletotrichum species invade into plant epidermal cell by penetration peg developed from melanized appressorium, followed by invasive hyphal extension. I reported nonadapted Colletotrichum fungi that showed an increased rate of melanized appressorium-mediated entry (MAE) into the pen2 mutant of nonhost Arabidopsis thaliana (hereafter Arabidopsis). It was also found that other MAE-type nonadapted Colletotrichum fungi with no penetration into the pen2 mutant invaded Arabidopsis in the presence of additional mutations such as edr1, gsh1, eds5, cas, and chup1 in the pen2 background. Thus, many immune components contribute to the preinvasive nonhost resistance (NHR) of Arabidopsis against Colletotrichum MAE, and PEN2-related defense takes priority over other defense pathways. Here, I show that among the above nonadapted fungi, Colletotrichum nymphaeae PL1-1-b exhibited relatively lower incompatibility with the nonhost Arabidopsis with increased MAE in each single mutant of edr1, gsh1, eds5, and cas, although other nonadapted fungi almost never invaded these single mutants. Based on the relationships between Colletotrichum MAE and the Arabidopsis immune-related components, Colletotrichum-Arabidopsis incompatibility and multilayered immunity in the preinvasive NHR of Arabidopsis are discussed in this study.